VISUAL MANAGEMENT AS ORGANISATIONAL AND APPLIED BASIS FOR MODERN ARCHITECTURAL PROJECTS - MAKATORA, Dmytro; KUBANOV, Ruslan; MYKHALKO, Anastasiia (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The study examines the characteristics of visual management as an organisational and applied basis for modern architectural and construction projects. It has been found that using visual tools in management can increase the level of perceiving and understanding information, facilitate communication between project participants, and ensure more accurate and efficient task performance. In the authors’ view, visual management may be a simple tool at first glance, but its value extends far beyond simple data visualisation. Visual management becomes the basis for making informed decisions, coordinating efforts and achieving project goals in a world where sharing and managing large amounts of information is critical. The article identifies visual communication, workspace organisation, idea visualisation, colour planning, remote site monitoring using cameras and drones, and the use of VR technologies for virtual tours as the main elements of visual management used in architectural and construction projects. Characteristics of the application of each of these elements in construction are identified. In particular, the article highlights the role of graphic and visual materials for communication between project participants, the importance of optimal workspace organisation on a construction site, the value of visualisation of ideas for better understanding of project concepts and plans, and the benefits of colour planning to indicate different aspects of construction. The article also describes the possibilities of the use of cameras, drones and virtual reality technologies for the remote control, monitoring and demonstration of projects. The article provides recommendations for introducing visual management elements into the activities of architectural and construction companies, including creating visual communication platforms, holding regular visual planning sessions, ensuring the availability of visual materials, and investing in staff training in visual management methods. As a result, visual management contributes to the efficiency, quality and competitiveness of companies in the sector and is an integral part of modern management of architectural and construction projects. The role of this approach in ensuring the successful implementation of construction projects will only increase with the further introduction of innovative visualisation technologies and methods.
Keywords: visual management; manager; architectural and construction projects; communication; visualisation; colour design; remote control; innovative technologies